2002
DOI: 10.1046/j.1365-2249.2002.01956.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of prophylactic, concurrent and therapeutic lactoferrin treatment on LPS-induced inflammatory responses in mice

Abstract: SUMMARYMice injected with endotoxin develop endotoxaemia and endotoxin-induced death, accompanied by the oxidative burst and overproduction of inflammatory mediators. Lactoferrin, an iron binding protein, provides a natural feedback mechanism to control the development of such metabolic imbalance and protects against deleterious effects of endotoxin. We investigated the effects of intraperitoneal administration of human lactoferrin on lipopolysaccharide (LPS)-induced release of tumour necrosis factor alpha (TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
100
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 49 publications
4
100
1
Order By: Relevance
“…Previous studies on LPS activated macrophages and models of sepsis also reported this inhibitory effect of Lactoferrin to moderate other proinflammatory mediators [9,37]. Certainly, the ability of Lactoferrin to inhibit LPS-induced production of TNF-α and IL-6 is present when Lactoferrin is administered prophylactically (and even therapeutically) [29], or even when given therapeutically. The anti-inflammatory effects of Lactoferrin may simply be attributed to its ability to disrupt LPS binding of CD14 [3,15].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies on LPS activated macrophages and models of sepsis also reported this inhibitory effect of Lactoferrin to moderate other proinflammatory mediators [9,37]. Certainly, the ability of Lactoferrin to inhibit LPS-induced production of TNF-α and IL-6 is present when Lactoferrin is administered prophylactically (and even therapeutically) [29], or even when given therapeutically. The anti-inflammatory effects of Lactoferrin may simply be attributed to its ability to disrupt LPS binding of CD14 [3,15].…”
Section: Discussionmentioning
confidence: 95%
“…There are no published reports directly examining toxicity of injected bovine lactoferrin when utilized as an adjuvant, however, high concentrations (5-10 mg/mouse) of bovine lactoferrin are often delivered in experiments examining LPS and bacterial insults in murine models of sepsis [51][52][53][54] with no overt or reported toxicity. Previous studies demonstrated that addition of lactoferrin to the BCG vaccine increased host protection against subsequent virulent MTB challenge as observed by a decrease in organ bacterial load and a reduction in pulmonary disease pathology.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-␣ levels peaked 1 h after LPS injection and ranged from 100 pg/ml (22) to 600 pg/ml (1) to 15,000 pg/ml (14). Reported serum IL-6 levels peaked between 2 and 4 h after LPS injection and ranged from 900 pg/ml (1) to 5,000 pg/ml (14) to 40,000 pg/ml (24). In a murine model of sepsis caused by P. aeruginosa pneumonia, serum IL-6 levels above 3,600 pg/ml were associated with 100% mortality, whereas levels below 1,200 pg/ml were associated with 100% survival (9).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the mouse strain, the source of endotoxin, and the cytokine assays used, considerable variations in the cytokine response were reported (1,14,22,24). TNF-␣ levels peaked 1 h after LPS injection and ranged from 100 pg/ml (22) to 600 pg/ml (1) to 15,000 pg/ml (14). Reported serum IL-6 levels peaked between 2 and 4 h after LPS injection and ranged from 900 pg/ml (1) to 5,000 pg/ml (14) to 40,000 pg/ml (24).…”
Section: Discussionmentioning
confidence: 99%